Influencing factors for repeated implantation failure after in vitro fertilization-embryo transfer: a meta-analysis - NIU Jinzhi, WU Xiaoyu, NING Yanjiao, FENG Yajing, SHAN Weiying (预防医学)
Objective: To systematically evaluate the influencing factors for repeated implantation failure (RIF) after in vitro fertilization-embryo transfer (IVF-ET) in China, so as to provide the evidence for prevention of RIF. Methods: Literature on influencing factors for RIF in China were retrieved from CNKI, Wanfang Data, VIP, China Medical Literature Service System, PubMed, Web of Science, Cochrane Library and Embase from inception to September, 2024. A meta-analysis was performed using RevMan 5.3 and Stata 14.0 softwares. Literature were excluded one by one for sensitivity analysis. Publication bias was evaluated using Egger's test. Results: Initially 4 836 relevant articles were retrieved, and 12 of them were finally included, with a total sample size of 11 554 individuals. There were 10 case-control studies, 1 cohort study, and 1 cross-sectional study; and 10 high-quality studies and 2 medium-quality studies. The meta-analysis showed that factors including advanced age (OR=1.121, 95%CI: 1.035-1.215), prolonged infertility duration (OR=1.237, 95%CI: 1.091-1.403), abnormal hysteroscopy findings (OR=2.205, 95%CI: 1.119-4.348), positive anti-nuclear antibody (ANA) (OR=2.393, 95%CI: 1.473-3.886), and positive anti-beta2 glycoprotein Ⅰ antibody (β2-GPⅠ-Ab) (OR=2.824, 95%CI: 1.987-4.013) were associated with an increased risk of RIF; while factors including the large number of embryos transferred (OR=0.309, 95%CI: 0.098-0.973), thicker endometrium (OR=0.601, 95%CI: 0.556-0.650), and higher granulocyte colony-stimulating factor (G-CSF) levels (OR=0.657, 95%CI: 0.511-0.845) were associated with a reduced risk of RIF. Conclusion: IVF-ET RIF is associated with age, infertility duration, number of embryos transferred, endometrial thickness, hysteroscopy findings, G-CSF levels, ANA and β2-GPⅠ-Ab.